2019
DOI: 10.1007/s11010-019-03667-9
|View full text |Cite|
|
Sign up to set email alerts
|

ROS and diseases: role in metabolism and energy supply

Abstract: Researches dedicated to reactive oxygen species (ROS) had been performed for decades, yet the outcomes remain controversial. With the relentless effort of studies, researchers have explored the role of ROS in biosystem and various diseases. ROS are beneficial for biosystem presenting as signalling molecules and enhancing immunologic defence. However, they also have harmful effects such as causing tissue and organ damages. The results are controversial in studies focusing on ROS and ROS-related diseases by regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
299
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 444 publications
(304 citation statements)
references
References 99 publications
1
299
0
4
Order By: Relevance
“…Usually, the intracellular ROS levels in cells are high when the lipid content is also high ( 131 ). ROS are important signaling molecules that act as a ligands or activate multiple cellular signaling pathways, such as heat shock factor protein 1, NF-κB, p53, PI3K-AKT and ERK/JNK/p38, thereby affecting cellular carbohydrate metabolism, mitochondrial function, apoptosis and necrosis, proliferation and cancer cell infiltration ( 132 135 ). At present, studies have found that ROS affect the formation and degradation of cellular lipids ( 12 , 23 , 64 , 136 ).…”
Section: Effects Of Lipid Droplets On Cellular Stress and Apoptosismentioning
confidence: 99%
“…Usually, the intracellular ROS levels in cells are high when the lipid content is also high ( 131 ). ROS are important signaling molecules that act as a ligands or activate multiple cellular signaling pathways, such as heat shock factor protein 1, NF-κB, p53, PI3K-AKT and ERK/JNK/p38, thereby affecting cellular carbohydrate metabolism, mitochondrial function, apoptosis and necrosis, proliferation and cancer cell infiltration ( 132 135 ). At present, studies have found that ROS affect the formation and degradation of cellular lipids ( 12 , 23 , 64 , 136 ).…”
Section: Effects Of Lipid Droplets On Cellular Stress and Apoptosismentioning
confidence: 99%
“…One of the factors that plays a complex role in these diseases is reactive oxygen species (ROS). Normally ROS are generated in the mitochondrial respiratory chain [ 3 ]. Excessive ROS induce oxidative stress causing lipid peroxidation that can lead to brain dysfunction and death [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…CCL4 is metabolized by liver CYPs to CCL 3• free radicals and lead to lipid peroxidation and oxidative stress. In normal condition, ROS is generated and eliminated by antioxidant defense system 23 . Cells can response to oxidative stress when exposed to ROS and electrophilic chemicals by expression of protective proteins to avoid harm to cells.…”
Section: Discussionmentioning
confidence: 99%